Guru Sebagai Fasilitator untuk Meningkatkan Motorik Kasar Anak Usia Dini dengan Permainan Bola - Karimah, Laila; Syafrida, Rina; Riana, Nancy (Jurnal Ilmiah Wahana Pendidikan, 2024)
Teacher-led ball games have a significant impact on the enhancement of gross motor skills in early childhood students. The early childhood phase is a critical period for the development of these skills, and teachers play a pivotal role in creating an engaging and enjoyable learning environment. This article employs quantitative research methods to investigate how teacher-led ball games can influence the growth of gross motor skills in young children. The research also underscores the significance of structured games in supporting motor skill development and providing an enjoyable and effective teaching approach, particularly for young students. The study's findings highlight that teachers can serve as facilitators in nurturing the gross motor skills of young children through ball games. Early childhood motor skills are of utmost importance as they encompass aspects such as neural, muscular, and cognitive abilities. Additionally, the teaching methodology implemented by teachers fosters an engaging and captivating learning experience, capturing the enthusiastic participation of students in the classroom